2021
DOI: 10.1186/s12884-021-03626-7
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of aberrant right subclavian artery for fetal chromosome aneuploidy in women of advanced maternal age

Abstract: Background In the entire population, an aberrant right subclavian artery (ARSA) is closely associated with chromosomal abnormalities. ARSA with additional ultrasonic findings would increase risk of chromosomal abnormalities. The risk of fetal chromosomal abnormalities increased exponentially with the maternal age. These risks in the advanced maternal age (AMA) group are uncertain. This study aimed to determine the incidence of ARSA in Chinese AMA and non-AMA women and the frequency of aneuploid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…In our data set, the incidence of abnormal karyotypes and clinically significant microarray results in the AMA group was 15.1% (8/53) and 24.5% (13/53), respectively, and in the YMA group, the incidence was 3.5% (10/287) and 8.4% (24/287), respectively. There is significant difference in the incidence rate of abnormal karyotypes and clinically significant microarray results between the two groups ( p < 0.05), our data also confirm the point 46 .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In our data set, the incidence of abnormal karyotypes and clinically significant microarray results in the AMA group was 15.1% (8/53) and 24.5% (13/53), respectively, and in the YMA group, the incidence was 3.5% (10/287) and 8.4% (24/287), respectively. There is significant difference in the incidence rate of abnormal karyotypes and clinically significant microarray results between the two groups ( p < 0.05), our data also confirm the point 46 .…”
Section: Discussionsupporting
confidence: 83%
“…An AMA was significantly associated with the incidence of chromosomal abnormality, particularly autosomal trisomies 45 . In addition, Chen LP, et al 46 showed that with combined ARSA and AMA, the likelihood of the incidence of abnormal karyotype increased, and the frequency of abnormal karyotype was much higher in the AMA group than that in the YMA Group.…”
Section: Discussionmentioning
confidence: 99%
“…Two were associated with other sonographic abnormalities (hypoplastic left heart and Dandy-Walker malformation). A Chinese study from 2021 17 specifically looked at the incidence of ARSA and the predictive value of ARSA for fetal chromosomal abnormalities in women of advanced maternal age (AMA). They retrospectively collected data from 13,690 singleton pregnancies, from 2015 to 2018.…”
Section: Prevalence Of Arsa In a High-risk Populationmentioning
confidence: 99%